2022
DOI: 10.18203/issn.2454-5929.ijohns20222161
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors of acute otitis media among infants in a tertiary care hospital in Rawalpindi: a descriptive cross-sectional study

Abstract: <p><strong>Background: </strong>Acute otitis media (AOM) is the second most common disease of childhood. Many factors play role in the causation of AOM. However, the research-based data on risk factors for AOM in infants is still inadequate. Objective were this study<strong> </strong>aimed to determine the risk factors for AOM in infants with AOM.</p><p><strong>Methods: </strong>This descriptive cross-sectional study was conducted among 189 infant patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 14 publications
0
0
0
Order By: Relevance
“…In their study, Khan et al, observed that infants between the ages of 9 and 12 months had the highest prevalence (41.28%) of AOM, probably due to different climates and geographic locations and high populations. 5 There was a bimodal peak distribution of age in the study, where 25.8% of cases were under the age of 10 years and 25.2% between 31 and 40 years. The age group of 71-80 years (0.3%) had the lowest patient population.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…In their study, Khan et al, observed that infants between the ages of 9 and 12 months had the highest prevalence (41.28%) of AOM, probably due to different climates and geographic locations and high populations. 5 There was a bimodal peak distribution of age in the study, where 25.8% of cases were under the age of 10 years and 25.2% between 31 and 40 years. The age group of 71-80 years (0.3%) had the lowest patient population.…”
Section: Discussionmentioning
confidence: 74%
“…This finding contrasts with one made by Khan et al, who observed that there were more men (55.02%) than women (44.98%) with AOM. 5 The majority (53.1%) of patients who visited the ENT OPD at AMCH were from Dibrugarh. Age, gender, the number of family members, economic status, play school, overcrowded housing, genetic factors, season, immunization status, immunological status, infective rhinitis, adenoids, and allergic rhinitis can all be risk factors for AOM.…”
Section: Discussionmentioning
confidence: 97%